WISATA GASTRONOMI: DALAM TRADISI MEGIBUNG DI KABUPATEN KARANGASEM - Ida Ayu Devi Arini; Made Novita Dwi Lestari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
This study aims to examine the meanings and values contained in the megibung tradition, and the development of the tradition to become an alternative for tourism development in Karangasem Regency through gastronomic tourism. The method used in this research is qualitative method. Primary data was obtained from interviews with several informants selected by purposive sampling, while secondary data was obtained from online publications. This study provides recommendations for gastronomic tourism that can be used as a potential alternative to be developed in Karangasem Regency. The potential of the megibung tradition as gastronomic tourism can be seen from its cultural attractions and supported by adequate accessibility, supporting facilities and good tourism institutions or organizations.Keywords: Gastronomic Tourism, Megibung Tradition.